Plastic waste as a feedstock for solar-driven H2 generation12. Issue 10 (23rd August 2018) - Uekert, Taylor; Kuehnel, Moritz F.; Wakerley, David W.; Reisner, Erwin
Abstract : Plastic waste is recycled to hydrogen using sunlight and a CdS photocatalyst. Abstract : Solar-driven reforming of plastics offers a simple and low-energy means to turn waste into H2 . Here, we report the efficient photoreforming of three commonly produced polymers – polylactic acid, polyethylene terephthalate (PET) and polyurethane – using inexpensive CdS/CdO x quantum dots in alkaline aqueous solution. This process operates under ambient temperature and pressure, generates pure H2 and converts the waste polymer into organic products such as formate, acetate and pyruvate. We further validate the real-world applicability of the system by converting a PET water bottle into H2 . This is the first demonstration of visible light-driven, noble metal-free photoreforming of plastic.